Answer:
12x^3+15x^2-12x+12
Step-by-step explanation:
P(x) = 12x^3 + 11x^2 - 9x + 10
Q(x) = 4x^2 – 3x + 2
P(x) + Q(x) = 12x^3 + 11x^2 - 9x + 10+ 4x^2 – 3x + 2
Combine like terms
=12x^3+11x^2+4x^2-9x-3x+10+2
=12x^3+15x^2-12x+12
Answer:
B. two
Step-by-step explanation:
Answer:
A sudents who take gym class
Step-by-step explanation:
the survey only asks for all the students enrolled in a gym class so they can compare with the data for all the students enrolled in the football team
He could have wrote -2.5 or -3.
Answer: 3 dollars for a book.
Step-by-step explanation: